The work of Glenn F. Webb - William E. Fitzgibbon (Mathematical Biosciences and Engineering)
It is my distinct pleasure to introduce this volume honoring the 70thbirthday of Professor Glenn F. Webb.The existence of this compiled volume is in itself a testimony of Glenn's dedication to,his pursuit of, and his achievement of scientific excellence.As we honor Glenn, we honor what is excellent in our profession.Aristotle clearly articulated his concept of excellence.``We are what we repeatedly do. Excellence, then, is not an act, but a habit."As we look over the course of his career we observe ample evidence ofGlenn Webb's habitual practice of excellence. Beginning with Glenn's first paper [1],one observes a constant stream of productivity and high impact work.Glenn has authored or co-authored over 160 papers, written one research monograph,and co-edited six volumes. He has delivered plenary lectures, colloquia,and seminars across the globe, and he serves on the editorial boards of11 archival journals. He is a Fellow of the American Mathematical Society.Glenn's scientific career chronicles an evolution of scientific workthat began with his interest in nonlinear semigroup theory and leads up tohis current activity in biomedical mathematics. At each stage we seeseminal contributions in the areas of nonlinear semigroups, functionaldifferential equations, infinite dimensional dynamical systems,mathematical population dynamics, mathematical biology and biomedical mathematics.Glenn's work is distinguished by a clarity and accessibility of exposition,a precise identification and description of the problem or model under consideration,and thorough referencing. He uses elementary methods whenever possiblebut couples this with an ability to employ power abstract methods whennecessitated by the problem.For more information please click the “Full Text” above.